วิธีตรวจหาการกัดกร่อนบนโพลทิพ - บุญชื่น, สมเจตน์; บุญศรี, อัษฎางค์; มุณีสว่าง, ไพศาล; แย้มเม่น, สุชาติ (Naresuan University Engineering Journal, 2014)
ในการผลิตฮาร์ดดิสก์ไดรฟ์มีขั้นตอนหนึ่งที่สำคัญคือการตรวจหาการกัดกร่อนของโพลทิพซึ่งทำหน้าที่เป็นหัวอ่านและเขียนของฮาร์ดดิสก์ไดรฟ์ ดังนั้นจึงต้องมีการทำงานที่มีความแม่นยำสูง โดยทั่วไปขั้นตอนนี้จะใช้สายตาของมนุษย์ในการตรวจหาการกัดกร่อนซึ่งมักเกิดความผิดพลาดได้เพราะว่าความเมื่อยล้า งานวิจัยนี้นำเสนอวิธีการตรวจหาการกัดกร่อนบนโพลทิพแบบอัตโนมัติภายในท็อปชิลด์กับการกัดกร่อนตามแนวขอบล่างท็อปชิลด์โดยใช้ตัวจำแนก 3 ลักษณะเด่น คือคุณลักษณะเด่น 1 ที่ใช้จำแนกพื้นที่กัดกร่อนภายในท็อปชิลด์ คุณลักษณะเด่น 2 ที่ใช้จำแนกตำแหน่งกัดกร่อนขอบล่างท็อปชิลด์ และคุณลักษณะเด่นแบบผสมผสานระหว่างคุณลักษณะเด่น 1 และ 2 ที่ใช้จำแนกการกัดกร่อนบริเวณท็อปชิลด์ จากผลการทดลองกับกลุ่มข้อมูลจำนวน 647 รูป พบว่า คุณลักษณะเด่นแบบผสมผสานซึ่งมีค่าความถูกต้องร้อยละ 96.75 ให้ค่าประสิทธิภาพในการจำแนกการกัดกร่อนมากกว่าคุณลักษณะเด่น 1 และ 2 ซึ่งมีค่าความถูกต้องร้อยละ 69.86 และ 93.51 ตามลำดับ Detection Method for Corrosion on the Pole Tip In hard disk drive manufacturing, one of important steps is corrosion detection on the pole tip that serves as both reading and writing heads of the hard disk drives. Thus, it must be worked with high accuracy. In general, the corrosion detection is performed by the human eyes, which can often fail to do because of the fatigue. This research presents automatic corrosion inspection methods. The inspected corrosion is within the top shield and along the bottom edge of the top shield by using three classification features: the first one is used for classifying corrosion area within the top shield, the second one is used for classifying corrosion position along the bottom edge of the top shield, and the last one which is a combination of the 1st and 2nd features is used for classifying the corrosion of the top shield. From experiment results with 647 pole tip images, it was found that the integrated feature with an accuracy of 96.75 provided higher efficiency of corrosion detection than both 1st and 2nd features with accuracies of 69.86 and 93.51, respectively.